2013
DOI: 10.1073/pnas.1218167110
|View full text |Cite
|
Sign up to set email alerts
|

The human gene connectome as a map of short cuts for morbid allele discovery

Abstract: High-throughput genomic data reveal thousands of gene variants per patient, and it is often difficult to determine which of these variants underlies disease in a given individual. However, at the population level, there may be some degree of phenotypic homogeneity, with alterations of specific physiological pathways underlying the pathogenesis of a particular disease. We describe here the human gene connectome (HGC) as a unique approach for human Mendelian genetic research, facilitating the interpretation of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
98
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2
1

Relationship

4
5

Authors

Journals

citations
Cited by 78 publications
(99 citation statements)
references
References 41 publications
1
98
0
Order By: Relevance
“…We found that biological proximity, as predicted by the human gene connectome, was greater among high-GDI genes and among low-GDI genes than for randomly selected human genes (P < 1.0 × 10 −5 for both sets) (15)(16)(17). This biological proximity suggests that high-GDI genes are functionally related to each other, as are low-GDI genes.…”
Section: Genes Found To Be Highly Mutated In Patients With Monogenicmentioning
confidence: 69%
See 1 more Smart Citation
“…We found that biological proximity, as predicted by the human gene connectome, was greater among high-GDI genes and among low-GDI genes than for randomly selected human genes (P < 1.0 × 10 −5 for both sets) (15)(16)(17). This biological proximity suggests that high-GDI genes are functionally related to each other, as are low-GDI genes.…”
Section: Genes Found To Be Highly Mutated In Patients With Monogenicmentioning
confidence: 69%
“…Finally, a consideration of copy number variation would also refine the calculation of the GDI (49). The rigorous study of mutational damage across human genes, at the genome-wide and population levels, together with other genome-wide approaches (11,15,50,51), should facilitate studies of human genetics, particularly for monogenic disorders.…”
Section: Discussionmentioning
confidence: 99%
“…bwh.harvard.edu/pph2/), which predicts the effect of an amino acid substitution on the structure and function of human proteins. BCL10 ranked very highly in the human gene connectomes of MALT1, CARD11, and CARD9 (17). A homozygous splice site Figure 4B).…”
Section: Resultsmentioning
confidence: 99%
“…A number of gene-and variant-level methods have been proposed for the analysis of WES data to select candidate variants in rare Mendelian disorders and more common traits (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13). These analyses benefit from the use of additional information, such as familial linkage, homozygosity rate, and ethnic background, which are commonly used in the study of inherited diseases (14)(15)(16)(17).…”
mentioning
confidence: 99%